Latent Message Playing the Game Free Fire As a Celebrity Factor and Fan Among Students - Amirul Mu'minin; Anis Rahmi; Intan Rizky Mutiaz (Journal of Visual Art and Design, 2025)
The use of digital applications, particularly online games on smartphones, increased significantly during the Covid-19 pandemic, especially in 2020. One popular game among students is Free Fire, a multiplayer game that enables virtual social interaction. This study aimed to identify latent messages emerging from the verbal and behavioral expressions of young players, as well as how digital figures like Rasyah Rasyid influence celebrity and fandom phenomena among high school students. This study employed virtual ethnography and Associative Concept Network Analysis (ACNA), using the University of South Florida (USF) association dictionary, to analyze Rasyah’s spontaneous speech during live-streamed gameplay. The findings revealed that the primary message emerging from Rasyah’s communication was the concept of ‘friend,’ which was the central node in the word association network, as it had the highest ODC score (0.24). These results indicate that communication within online games extends beyond technical or competitive functions and plays a crucial role in fostering emotional closeness and social bonds. Such interactions contribute to the development of parasocial relationships between online idols and their audiences. This study provides insight into how digital popular culture, game-based communication, and visual personas influence the identities and aspirations of high school students in the digital era.